Pancreatic Actinomycosis as a Cause of Retroperitoneal Fibrosis in a Patient with Chronic Pancreatitis. Case Report and Literature Review - Sahay, Samir John; Gonzalez, Hector Daniel; Luong, Tu Vinh; Rahman, Sakhawat Hussain (JOP. Journal of the Pancreas, 2010)
Context Chronic alcoholic pancreatitis is a debilitating disease that is often complicated by pseudotumoral changes of the pancreas, retroperitoneal fibrosis, and pancreatic cancer. Actinomycosis is an uncommon intra-abdominal infection and its association with chronic pancreatitis has been rarely reported. Case report We present a case of a patient with progressive long standing chronic pancreatitis who develops pseudo-tumoural changes and retroperitoneal fibrosis associated with actinomycosis. Conclusion This is a rare presentation of actinomycosis, posing a diagnostic challenge to the clinician, with important therapeutic implications. Image: Basophilic spherical mass with a radiating border of eosinophilic clubs.